Exploration and Interpretation of Current Bibliometric Data: Ethical Implications of Artificial Intelligence. - Cristian Roosevelt Sáenz De Viteri Anzules; María Emilia Luna Quintero; Givanna Anahí Triviño Fuentes; María Emilia Rosas Flores (PODIUM, 2025)
This study submerges into the bibliometric data of AI ethics and explores the different conclusions regarding the ethical implications of AI to answer what is the current state of knowledge on the ethical dilemmas that AI brings, while discussing what are the ethical principles or conclusions that are being identified as ethical in AI implementation. By gathering the data from Scopus and Web of Science, using keywords of ethics, AI, business and social, in order to be able to identify the ethical implications of AI in both society and companies. Then analyzing it using Litmaps, Tree of Science, Core of Science, and Vos Viewer. Concentrating on different sources of the field reveals important information of AI ethics: the countries that are researching the topic, the journals, the years of publications, the main keywords within the field, and other fields or areas of studies related to it. The observations can serve as potential directions for future research, policies, and more.